Thermodynamics of structurally disordered s–d model - Rudavskii, Yu.K.; Ponedilok, G.V.; Dorosh, L.A. (Condensed Matter Physics, 2005)
Spin-electron exchange model is generalized and used for description of
magnetic states of amorphous substitutional alloys with the structural disorder
of the liquid type. A scheme of consistently accounting for the contributions
of structural fluctuations to the thermodynamic functions and observable
quantities is considered. Using the perturbation theory, the functional
of thermodynamic potential is constructed as a functional power series.
In the random phase approximation (RPA), the grand thermodynamic
potential of the model is calculated. Self-consistency conditions are given,
from which equations for magnetizations and critical temperature of the
paramagnetic-ferromagnetic transition are obtained. Спін-електронна обмінна модель узагальнюється і застосовується для опису магнітних станів аморфних сплавів з рідиноподібним
типом структурної невпорядкованості. Розглянута схема послідовного врахування вкладу структурних флуктуацій у термодинамічні
функції та спостережувані величини. За теорією збурень побудовано функціонал термодинамічного потенціалу у формі функціонального степеневого ряду. У наближенні хаотичних фаз (RPA)
розраховано великий термодинамічний потенціал моделі. Записані
співвідношення самоузгодження, з яких знаходяться рівняння для
намагніченостей та критичної температури переходу “парамагнетик-феромагнетик”.